2009
DOI: 10.1203/pdr.0b013e3181991511
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Augments Bilirubin Toxicity in Rat Cortical Neuronal Culture

Abstract: Premature infants are at risk for bilirubin-associated brain damage. In cell cultures bilirubin causes neuronal apoptosis and necrosis. Ibuprofen is used to close the ductus arteriosus, and is often given when hyperbilirubinemia is at its maximum. Ibuprofen is known to interfere with bilirubin-albumin binding. We hypothesized that bilirubin toxicity to cultured rat embryonic cortical neurons is augmented by coincubation with ibuprofen. Incubation with ibuprofen above a concentration of 125 g/mL reduced cell vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…These findings supports the previous studies that UCB has a dual effect on astrocyte cells, being neuroprotective at lower concentrations, but neurotoxic at higher concentrations. Furthermore, the present study also demonstrated that IC 50 36,38 .…”
supporting
confidence: 81%
“…These findings supports the previous studies that UCB has a dual effect on astrocyte cells, being neuroprotective at lower concentrations, but neurotoxic at higher concentrations. Furthermore, the present study also demonstrated that IC 50 36,38 .…”
supporting
confidence: 81%
“…Furthermore, the viability of the cells was not affected by a 72 h exposure to up to 300 μM of 1 or 2 (Figure S28). These data confirm the low toxicity of ibuprofen (1) 3,23 and also demonstrate a low toxic potential of sila-ibuprofen (2), as no differences in the parameters determined were observed (Figure S28). In addition, the exposure of C6 cells to 1000 μM of 1 or 2 did not lead to any obvious change in cell morphology or to any significant increase in extracellular lactate dehydrogenase activity, demonstrating that these high concentrations were not toxic to the cells either.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…38 Indeed, a recent study showed that ibuprofen augments bilirubin toxicity in rat cortical neuronal culture. 43 The clinical significance of this potential neurotoxicity remains unknown. Data on the long-term outcome of preterm infants randomized to ibuprofen would be helpful in clarifying these concerns.…”
Section: Introductionmentioning
confidence: 99%